ADMINISTRATIVE PERSONNEL OF UNIVERSITY OF MIDDLE AND LOWER LEVEL: PROCEDURE AND SELECTION CRITERIA - Zhabenko, Oleksandr (Educological discourse, 2020)
In the article analyzed the procedures and criteria for selecting candidates for middle and lower administrative positions at universities in Ukraine and the Netherlands. Detected differences in the process of selection of administrative personnel of university of middle and lower level: in the use of criteria for selection of candidates (in Ukraine – formal criteria for selection of candidates, there are no criteria for determining the level of competence of the candidate, his professional and moral or ethical qualities; universities in the Netherlands use «job profiles», which contain functional responsibilities, qualification or competence requirements of the applicant, and the main criteria for selecting candidates are their authority both in academic and non-academic environment, level of competence, professional and moral and ethical qualities); in appointment to the position (in Ukraine, the rector appoints the dean (director) with the consent of the public self-government body of the faculty (institute) and appoints all administrative personnel of middle and lower level; in the Netherlands, the university’s executive council appoints deans, deans appoint heads of departments; representatives of students of the faculty are involved in the work of the dean’s office). Proposed to improve the process of selection of candidates for administrative personnel of university of middle and lower level in Ukraine: to develop job profiles (with an exhaustive list of criteria for clarifying the competence of the applicant; questions to determine the level of competence and personal qualities of candidates); introduce the practice of submitting portfolios by applicants for positions (with information on training, enhancement of competence, professional experience and achievements, etc.) for prior review.